Potentials and development of orchid species and medicinal plant in Tourism Loop-Trail Cikiniki-Citalahab, Gunung Halimun-Salak National Park - Aditya Hani; Tri Sulistyati Widyaningsih; Ratna Uli Damayanti (Jurnal Ilmu Kehutanan)
Halimun-Salak Mountain National Park (HSMNP) is one of the largest tropical rain forests in,West Java which has a high biodiversity value. Biodiversity type includes ornamental and medicinal plants. Both of these are the Non-Timber Forest Products (NTFPs) with the potentiality to be economically developed. This research aimed to identify orchide species and medicine plants in the HSMNP.  This study is an initial step on ex situ conservation of forest plant species. Studies were conducted in the forest area between Cikaniki and Citalahab area in TNGHS which has an altitude of 1000-1900 m asl. Data collection was performed by exploration and identification of plants. Exploration results indicated the presence of 68 of orchid species and 14 species of medicinal plants. These species have mostly been used by the forest community for traditional medicinal uses. Potency of ornamental and medicine plants should be preserved and developed through ex situ conservation.  These activities can be used as a learning medium for the community with regard to cultivation techniques of orchides and medicinal plants.